Robot-assisted liver resection - Aselmann, H.; Moeller, T.; Kersebaum, J. -N.; Egberts, J. H.; Croner, R.; Brunner, Michaela; Grützmann, Robert; Becker, T. (Chirurg, 2017)
Robotic liver resection can overcome some of the limitations of laparoscopic liver surgery; therefore, it is a promising tool to increase the proportion of minimally invasive liver resections. The present article gives an overview of the current literature. Furthermore, the results of a nationwide survey on robotic liver surgery among hospitals in Germany with a DaVinci system used in general visceral surgery and the perioperative results of two German robotic centers are presented.
EVALuna2:15283